Effect of Climate Change on Wetland Areas in West Iraq Using Satellite Data and GIS Techniques - Hassan, Waqed H.; Khazaal, Suhail T.; Al-Shammari, Musa H. (Salehan Institute of Higher Education, 2024)
Iraq is considered to amongst those countries in the Middle Eastern region that are most exposed to the effects of climate change, which will have notable effects on wet areas and lakes. Natural or industrial water resources must be paid particular attention due to their importance in preserving environmental and biological systems, in addition to their economic and social importance. As a result of the effects of climatic change, water resources in Iraq have seen a multitude of changes. The aim of this study is to determine changes in the wetland area around AL-Razzaza Lake, Karbala province, Iraq, during the years 2000, 2005, 2010, 2015, and 2023. Landsat 5 satellite data from 2000, 2005, and 2010, and Landsat 8 and 9 data for 2015 and 2023, respectively, were used in this analysis, which was conducted using NDWI as a free, open-source program (ArcMap 10.8) to detect these changes; NDWI is a natural water anisotropy index used to detect the surface area of bodies of water in satellite images. The results revealed a clear decrease throughout the study period, as the wetland area of the lake in 2000 was 1189.7 km2, which represents a decrease of 34.3% compared to the total area of the lake (1810 km2); it decreased by 52.7% in 2005 (855.5 km2) and continued to decrease for 2010, 2015, and 2023, by 79.2%, 80%, and 85%, (376.5 km2, 362.9 km2, and 270.4 km2, respectively). The wetland area of Al-Razzaza Lake decreased between 2000 and 2023 by 919.3 km2, that is, an average of 40 km2per year. It was found that the lake wetland area sharply declined over the study period due to a lack of water surface resources via the Euphrates River, as well as climatic changes and poor water resource management. It is anticipated that the lake will lose more than half its current wetland area by 2040 if the current decline continues. These results are considered important in terms of preparing a strategic plan to preserve water bodies and wet areas in Iraq, including Al-Razzaza Lake. Remote sensing and GIS technologies have played a major and essential role in detecting such changes. Doi: 10.28991/CEJ-2024-010-09-013 Full Text: PDF